Between Life and Spirit: The Place of Plants in Hegel’s Dialectic of Nature - de Souza, Grégori; Oliveira, Jelson (ETHICS IN PROGRESS, 2025)
The aim of this paper is to examine the place of plants in G.W.F. Hegel’s philosophy, highlighting their relevance for understanding the relationship between life and spirit within the Hegelian dialectical system. We will demonstrate how plants are situated in the context of the Philosophy of Nature proposed by the author, emphasizing how, despite being understood through their “incomplete subjectivity” and limited individuality (as there is no individual cohesion due to the separation of their organs), it is still possible to conceive of the basic metabolism of plants as the first expression of the dialectical relationship between inner life and the external environment. In this sense, plants represent a special transitional moment in the progressive realisation of the Idea. We will analyze how plants, for Hegel, embody a universal form of life – selforganized and oriented toward its relationship with the environment – that serves as a point of mediation, or the nexus, between the objectivity of nature and the subjectivity of spirit, which will develop more fully in animal life, especially human life. As we intend to demonstrate, referring to the subjective incompleteness of plant life does not deny it a place in the very history of spirit.